PENERAPAN ACTION DAN RESULT CONTROL UNTUK MENGATASI MOTIVATIONAL PROBLEMS PADA BANK NTT KCU SURABAYA - Nensi Laurence Nggai; Wiyono Pontjoharyo (CALYPTRA, 2018)
Absract - This study aims to address the existing motivational problems in Bank NTT KCU Surabaya. The concept used to overcome the motivational problems is by applying a management control system that focuses on the action and result control. The type of research used is applied research with qualitative approach method. This research tries to give recommendation on the motivational problems that occur in business entity, in this case research object is Bank NTT KCU Surabaya. The research finds five motivational problems that need to be addressed at Bank NTT KCU Surabaya. Motivational problems occur due to the weakness of formal business control system.